Упростите выражение:

(x+6)*(x+5)

(a-4)*(a+1)

(2-y)*(y-8)

(a-4)*(2a+1)

(2y-1)*(3y+2)

(5x-3)*(4-3x)

2

Ответы и объяснения

2012-02-02T13:19:52+04:00

1) х2+5х+6х+30=х2+11х+30

2) а2+а-4а-4=а2-3а-4

3) 2у-16-у2+8у=10у-16-у2

4) 2а2+а-8а-4=2а2-7а-4

5) 6у2+4у-3у-2=6у2+у-2

6) 20х-15х2-12+9х=29х-15х2-12

х2; а2..15х2..- это значит в квадрате: х в квадрате; а в квадрате..15х в квадрате...

 

Лучший Ответ!
2012-02-02T13:48:38+04:00

1) (x+6)*(x+5)=x^2+5x+6x+30= x^2+11x+30

2) (a-4)*(a+1)=a^2+a-4a-4=a^2-3a-4

3) (2-y)*(y-8)=2y-16-y^2+8y=y^2+10y-16

4) (a-4)*(2+1)= 2а2+а-8а-4=2а^2-7а-4

5) (2y-1)*(3Y+2=6у2+4у-3у-2=6у^2+у-2

6) (5x-3)*(4-3X)=20х-15х2-12+9х=-15х^2-29x-12